Analyzing Worn-Out Texture Regeneration from Urban Branding Perspective Using Structural Equation Modeling (SEM) (Case Study: Worn-Out Texture of Shahr-e-Kord) - Dvood Mahdavi; Ali Mohammadi Gojani; Waliullah Nazari (برنامه ریزی فضایی, 2024)
AbstractUrban regeneration, a contemporary approach to revitalizing worn-out urban areas, has a tremendous impact on the quality of life and sustainability of residents. When combined with creative strategies like urban branding, this approach can spur the growth and enhancement of dilapidated urban fabric, ultimately boosting a city's competitiveness. The primary aim of this research was to analyze and model the regeneration of the worn-out urban areas of Shahr-e-Kord from urban branding perspective. The worn-out tissue of Shahr-e-Kord was selected as a case study. This was an applied research study with a descriptive-correlational purpose. The data were collected through documentary and field methods. The statistical population included 8292 residents of Shahr-e-Kord worn-out fabric with a sample of 367 participants selected using Cochran's formula. The questionnaires were completed by 400 participants using cluster sampling and simple classification. Structural Equation Modeling (SEM) in PLS software was employed for data analysis. The results indicated that physical and spatial interventions (path coefficient of 0.508) had the most significant impact on the effective regeneration of Shahr-e-Kord worn-out fabric followed by marketing and place promotion components (coefficient of 0.355). Non-spatial interventions (0.214) and indirect marketing effects (0.180) ranked lower in influence. Furthermore, the findings demonstrated a strong, positive, and significant influence of the branding variable on the regeneration of the worn-out urban fabric with an impact coefficient of 0.833. This suggested that a change in urban branding factors and components could lead to favorable changes in urban regeneration variables. Keywords: Urban Regeneration, Urban Branding, Dilapidated Fabric, Shahr-e-Kord. IntroductionUrban regeneration approach is one of the newest paradigms for revitalizing worn-out urban areas. This approach has a significant impact on the quality of life and sustainability of residents. When combined with creative strategies like urban branding, it can spur the growth of dilapidated urban fabric and enhance a city's competitiveness. In addition to its positive effects on developing and promoting cities' competitive advantages, this strategy is also recommended as a suitable tool for recreating and revitalizing historical neighborhoods. Therefore, creating an integrated framework that considers both branding and urban regeneration strategies can yield highly favorable results. Based on this, the primary aim of the current research was to explain the model of how the components of an urban branding strategy influenced the success of urban regeneration in the dilapidated context of Shahr-e-Kord. Materials & MethodsThis research was an applied study with a descriptive-correlational approach. The data collection methods used were documentary and field-based. The statistical population comprised all residents of Shahr-e-Kord's dilapidated urban fabric, totaling 8292 people. Using Cochran's formula, a sample of 367 individuals was selected and the questionnaires were completed by 400 participants through cluster sampling and simple classification. The research variables were drawn from two primary indicators of urban regeneration, including 4 sub-indices (economic, socio-cultural, physical, and environmental), and urban branding, including 4 sub-indices (physical-spatial interventions, non-spatial branding interventions, marketing and place promotion, and indirect branding effects). The validity and reliability of the research instrument were then assessed. Finally, the impact of urban regeneration on branding was modeled. To analyze the research data, several techniques were employed. First, the normality of the data was determined using the Kolmogorov-Smirnov test in SPSS software across the research variables. Next, the construct validity of the research variables and their resulting indices were examined using confirmatory factor analysis. Lastly, to answer the research questions, Structural Equation Modeling (SEM) was conducted using the Partial Least Squares (PLS) approach in the Smart-PLS software environment. Research FindingsThe data were analyzed using the ESM method. The validity assessment results showed that all research variables had a value of greater than 0.4, indicating maximum validity. Additionally, the reliability of the available options demonstrated high reliability of the research components through the application of various methods (AVE and CR). The findings revealed that among the urban branding components, the component of physical-spatial interventions had the greatest impact on the effective regeneration of Shahr-e-Kord's dilapidated urban fabric. This component with a path coefficient of 0.508 explained a little more than half of the changes in urban regeneration. This suggested that physical and spatial reforms had to be made through branding tools to regenerate Shahr-e-Kord's worn-out urban fabric. Other influential factors on urban regeneration were marketing and place promotion (0.355), non-spatial interventions (0.214), and indirect marketing effects (0.180) in order of importance. Furthermore, the results from the final SEM showed a positive, strong, and significant influence of the branding variable on the regeneration of the worn-out urban fabric with an influence coefficient of 0.833. This meant that a one-unit change in the factors and components of urban branding had led to a favorable change in the variables of urban regeneration. Discussion of Results & ConclusionInefficient and dilapidated urban areas, such as the one examined in this study, make up a substantial portion of the surface area of cities across the country. These areas pose significant challenges for urban management and planning due to their numerous economic, social, physical, functional, transportation, and environmental problems. The present study aimed to model the impact of urban regeneration on the branding of Shahr-e-Kord's dilapidated urban fabric. The analysis of the variables and items (based on field and experimental studies in the area) indicated the existence of severe problems, dissatisfaction, and deep weaknesses in the worn-out fabric of the study area. The theoretical average of less than 3 for about 90% of the variables confirmed this, suggesting that the concepts of regeneration and urban branding in these communities were weak and indicated a lack of subjective satisfaction among the residents. Furthermore, the results from the SEM showed a significant and strong impact of the component of primary urban branding on regeneration, where changes in one component led to significant changes in the other. This implied that the factors of social, economic, physical, and environmental regeneration and revitalization in Shahr-e-Kord's dilapidated urban fabric had a substantial effect on increasing the stability and preparedness of this fabric for successful branding of the area. In conclusion, the findings highlight the critical role of urban branding in the regeneration of dilapidated urban areas, emphasizing the need for comprehensive, integrated strategies that address the multifaceted challenges of these communities. Successful urban regeneration and branding can contribute to the overall development and revitalization of deteriorated urban fabrics.